1998
DOI: 10.1037/0012-1649.34.6.1220
|View full text |Cite
|
Sign up to set email alerts
|

Like mother, like child: Intergenerational patterns of age at first birth and associations with childhood and adolescent characteristics and adult outcomes in the second generation.

Abstract: A 30-year follow-up of 1,758 inner-city children and their mothers in the Pathways to Adulthood Study revealed significant associations in transgenerational timing of age at 1st birth between mothers and their daughters and sons. Intergenerational age patterns were associated with the children's family and personal characteristics during childhood and adolescence and self-sufficiency at age 27-33. Continuity in teenage parenthood was associated with family and personal characteristics unfavorable for optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
1
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(151 citation statements)
references
References 27 publications
6
139
1
4
Order By: Relevance
“…Poverty level (Hardy et al 1998) represents the ratio of the mother's annualized income to the poverty level based on the Annual Statistical Supplement to the Social Security Bulletin (US DHHS, 1993). All confounders, except the age of the child, were based on the mother's self-report.…”
Section: Adult Psychopathology and Illness-depression Was Measured Wimentioning
confidence: 99%
“…Poverty level (Hardy et al 1998) represents the ratio of the mother's annualized income to the poverty level based on the Annual Statistical Supplement to the Social Security Bulletin (US DHHS, 1993). All confounders, except the age of the child, were based on the mother's self-report.…”
Section: Adult Psychopathology and Illness-depression Was Measured Wimentioning
confidence: 99%
“…Childhood poverty and socio-economic disadvantage has been shown to be clearly linked with early age at first birth and with the context of childbearing and both are linked to subsequent adult social disadvantage (Kiernan 1995;Hobcraft and Kiernan 2001;Kiernan 2002;Hardy et al 1998;Duncan et al 1998;Hobcraft 2004). Childhood academic test scores have been shown to have powerful residual associations with a wide range of adult disadvantages, net of qualification levels (Hobcraft 2000) and academic ability has been found to be very strongly associated with the timing of childbearing (Kiernan and Diamond 1983;Kiernan 1997;Upchurch et al 2002) and the context of childbearing (Kiernan 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Others have examined outcomes for adolescents born to teenage mothers who were not part of Furstenberg's sample with mixed results East & Felice, 1990;Fergusson & Woodward, 1999;Hardy, Astone, Brooks-Gunn, Shapiro, & Miller, 1998). Dubow and Luster (1990) used the NLSY to examine the outcomes of 721 adolescents born to teenage mothers.…”
Section: Strategy That Incorporates Social Structural Change Efforts mentioning
confidence: 99%
“…They found that teenage mothers had lower educational attainment than older mothers, and their adolescent children had more scholastic problems than youths of adult mothers. Hardy et al (1998) examined outcomes of children born to teenage mothers in a longitudinal study of over 1,500 urban and mostly African American mother/child pairs. They found more negative outcomes among children of teenage mothers including teenage parenthood, distress, antisocial behaviors, and leaving high school before graduation than among those with parents over 20 years of age.…”
Section: Strategy That Incorporates Social Structural Change Efforts mentioning
confidence: 99%